Target polypeptide of a carcinogen is associated with normal mitosis and carcinogen-induced hyperplasias in adult hepatocytes. - Custer, R P (1984)
Normal rat liver cytosol was found previously to contain a 14,000-dalton polypeptide that is the principal target of the carcinogen N-2-fluorenylacetamide (2-acetyl-aminofluorene) early during hepatocarcinogenesis. By using antiserum that identifies the 14,000-dalton polypeptide in liver cytosol, an immunologically related 17,500-dalton polypeptide was shown to be present in isolated normal liver nuclei, tightly bound to chromatin. We report here that the 14,000-dalton polypeptide is associated with cell multiplication in normal adult hepatocytes. Of 150 hepatocytes in five stages of mitosis, all invariably displayed a greatly increased concentration of the 14,000-dalton polypeptide in cytoplasm, compared to hepatocytes in interphase, by immunostaining with peroxidase-antiperoxidase complex. In contrast, mitosis did not appear to affect the level of the 17,500-dalton polypeptide in nuclei. A small population of high-polyploid hepatocytes with large nuclei had elevated intensities of cytoplasmic immunostain that approached that in mitotic cells. The increased level of discernible 14,000-dalton polypeptide target of the carcinogen in cytoplasm is a marker of the rare mitotic hepatocytes in normal adult rat liver. Ingestion of the liver carcinogen N-2-fluorenylacetamide for 5 wk or an azocarcinogen, 3'-methyl-4-dimethylaminoazobenzene, for 4 wk brought about early foci of hyperplastic hepatocytes in which there was a great overload of detectable 14,000-dalton target polypeptide in their cytoplasm and a near absence of the 17,500-dalton polypeptide in most nuclei. In contrast, the cytoplasm and nuclei in surrounding morphologically nontransformed hepatocytes of livers of the carcinogen-fed rats immunostained to a much smaller degree than in normal adult hepatocytes. Removal of the azo-dye carcinogen for 4 wk resulted in the disappearance of most hyperplastic foci. A few foci did persist and had similar apparent abnormal levels of the two polypeptides. The high concentration of discernible 14,000-dalton target polypeptide in the cytoplasm of hepatocytes in the hyperplastic foci correlates with their known proliferation, whereas the low cytoplasmic level in the surrounding hepatocytes is consistent with the known inhibition of their mitosis by these carcinogens. The collected evidence appears to joint together a chemical carcinogen, a cytoplasmic principal target polypeptide, a chromatin-bound polypeptide, mitosis in normal adult hepatocytes, early and persistent hyperplastic foci caused by carcinogens, and the inhibition of mitosis by carcinogens in surrounding parenchyma in preneoplastic livers.